(untitled) (Philological Studies, 2019)
The starting point of this paper is the contemporary reception of the almanac Srpkinja [The SerbianWoman] from the viewpoint of social and literary theories. We outline an overview of the interest for the poetics and ornaments of female handicrafts in the context of Serbian folk culture, folklore art and national history of literature. We stress the archetypal origins and the folklore paradigm of the motifs, the symbolic potential of the weaver, needlewoman and knitter figures, and the creative principle of weaving as writing (and vice versa) is regarded in the light of autopoetic writings and literary theoretical concepts.